Migration to the Prague Cities in the Context of the Thirty Years War. Social Aspects and Town Hall Practice (Theatrum historiae, 2015)
In an effort to move us towards a better understanding of urban society transition as a background to the 17th century ‘General Crisis’, this paper examines the main aspects of incomers’ social strategy in their endeavour to become townsmen. According to the analysis regarding new burghers of Prague during that period, we also should take into account the impact of long-term issues on the development of the burgher society and factors of integration. Secondly, this paper focuses on the political and confessional changes that fundamentally influenced urban self-government and subsequently each immigrant’s aspiration to burgess-ship.
Keywords: Early Modern times; townspeople; migration; social strategy; Prague